Spatial distribution and health risk assessment of fluoride in groundwater in the oasis of the Hotan river basin in Xinjiang, China - Ling Li; Long Ma; Zhilin Pan; Juan Xu; Fei Chen; Changde Yang; Yidan Yin (Scientific Reports)
Abstract High fluoride groundwater is a global environmental and public health issue. To explore the effects of fluoride in groundwater in the oasis of the Hotan River Basin in Xinjiang on human health, this study analyzed the content and spatial distribution of fluoride in groundwater. Moreover, health risk assessment was performed using the Monte Carlo method based on the Unite States Environmental Protection Agency (USEPA) model. The results revealed that the groundwater in the Hotan River Basin oasis has an average F− content of 1.04 mg·L−1, with an exceedance rate of 35.2%. High-fluoride groundwater is typically characterized by a high HCO3 − content, low Ca2+ content relative to Mg2+ content, and the presence of hydrochemical types of Cl·HCO3-Na and HCO3-Na. The hazard quotient (HQ) of fluoride in groundwater > 1 for children and adults in Lop County, Karakax County, and Hotan city and for children in Hotan County. In the study area, the 1–95% quantile certainty of HQ is greater for children (58.30–38.74%) than for adults (52.65–28.26%). Therefore, most residents in the oasis are exposed to the nononcogenic health risks of fluoride in groundwater via the water drinking pathway, with children being highly sensitive. The fluoride content of groundwater in the study area significantly influences the nononcogenic health risk assessment for residents, with a variance contribution rate of 87.8–94.3%. Therefore, reducing the fluoride content in groundwater should be prioritized in decision-making regarding the safety of drinking water in the oasis.